Inhibition of Staphylococcus aureus by the cotton fabrics treated with the crude finish produced from Streptomyces sp. strain AC4 - Pook-In, Grissana; Seansupa, Khwanla; Upakut, Sorawit (Journal of Food Health and Bioenvironmental Science, 2019)
Streptomyces sp. isolated strain, AC4, showed the characteristic including significant growth for 3-7 days, the ability to produce the purple-like pigment in SCB and the substance to inhibit S. aureus growth. The crude samples of AC4 growth presented the purple suspension in SCB. The AC4 cultured suspension including the supernatants and the cell pellets were separated and pasteurized for test the thermal stability of the vegetative cells and spores of AC4, and the ability of the crude extract to inhibit the S. aureus. The results showed that the Streptomyces sp. AC4 crude samples could inactive its cells and spore by the temperature for pasteurization at 73 °C. Furthermore, the ability to inhibit the S. aureus had remained with the S. aureus inhibited zone. Then the coating steps of the cotton fabrics were performed by the simply heat dyeing at 70 °C with the crude finish (the cracked-cell pellets mixed with the supernatants 1:10 W/v). The results indicated that the antibacterial agents could immobilize with the treated fabrics by the clear zone of ability to against S. aureus by AATCC 147-2004 test was measured as 4.5 mm. In addition, AATCC 100-2004 test, the results of % reduction showed that the treated fabrics could reduce S. aureus growth as 100% for contact time 12 and 24 h. Streptomyces sp. AC4 crude finish as the natural finish by its self has the characteristic which could pasteurize and be environment friendly that might be useful to improve the improperly effluents.